Acute pancreatitis caused by duodenal bezoar and treated with endoscopic procedures. Issue 1 (30th September 2022) - Suzuki, Naoya; Furuya, Ryosuke; Otsuka, Tsuyoshi; Miyazaki, Hiroshi; Okano, Hiromu; Komatsu, Tatsuji; Yamada, Eiji; Yamaguchi, Yuka
Abstract : Background: Acute pancreatitis triggered by causative agents, including alcohol consumption, gallstones, dyslipidemia, drugs, and infection, is frequently addressed. However, reports of acute pancreatitis caused by duodenal bezoars are limited. Case Presentation: A 75‐year‐old man experiencing abdominal pain and frequent vomiting was transferred to our hospital. His medical records presented history of diabetes, hypertension, dyslipidemia, and gastric cancer surgery. Computed tomography of the abdomen indicated duodenal dilatation, enlarged pancreas, and fluid retention, with no bile duct stones present. Minor bleeding and duodenal bezoar were endoscopically detected with esophagogastroduodenoscopy (EGD). He was diagnosed with severe acute pancreatitis caused by a bezoar and admitted to the intensive care unit. The duodenal bezoar was dissected and removed with three repetitions of EGD, and the patient was discharged without any complications. Conclusion: Herein, we report a case showing that endoscopic procedures could be effective treatment options in severe pancreatitis caused by duodenal bezoars. Abstract : This case report highlights the importance of using EGD to diagnose and treat rare cases of acute pancreatitis caused by duodenal bezoars. In particular; examination of the causative agents of acute pancreatitis may lead to the establishment of a treatment strategy for each cause.